Anti-Angiogenesis Therapy of Cancer Cells using 153Sm-Bevasesomab - Yavari, Kamal (Emerging Science Journal, 2018)
Purpose: Angiogenesis is essential for tumor growth or metastasis. Avastin is a monoclonal antibody that is used in treating angiogenesis. We labelled this monoclonal antibody with samarium153 and performed in vitro quality control tests as a first step in the production of a new radiopharmaceutical.Material and Methods: For a successful radiolabeling, we chose DOTA-NHS as the bifunctional chelating agent and optimized radiolabeling condition with modifications of the factors such as reaction time and molar ratio which are known to be very critical in radiolabeling. The efficiency and in vitro stability of antibody labelling were determined using thin layer chromatography. The integrity of the radiolabeled antibody was checked by SDS-PAGE. Biodistribution study of 153Sm-DOTA –avastin was carried out in BALB/c mice at 2, 24, 48 and 72 hours after injection. Immunoreactivity and toxicity of the complex were tested on colon cancer cell line by MTT.Results: The efficiency of antibody labelling was more than 99%. The in vitro stability of the labelled product in human serum after 120h was 78 ±2%. There was no fragmentation in the labelled antibody during SDS-PAGE protocol. The highest of %ID/g was observed in the blood, liver, lungs and spleen. The immunoreactivity of the complex was 89±1.4%. At a concentration of 1 nM, the complex killed 70±3% of SW480 cells. At 1.9 nM, 90±5% of the cells were killed.Discussion: The monoclonal antibody avastin against angiogenesis was effectively radiolabeled with 153Sm. The results showed that the new complex could be considered a promising tracer for noninvasive delineation of angiogenesis.